A novel educational outreach approach to teach Hands-Only Cardiopulmonary Resuscitation to the public. (July 2017) - Chang, Mary P.; Gent, Lana M.; Sweet, Merrilee; Potts, Jerry; Ahtone, Jeral; Idris, Ahamed H.
Abstract: Review: The American Heart Association set goals in 2010 to train 20 million people annually in cardiopulmonary resuscitation and to double bystander response by 2020. These ambitious goals are difficult to achieve without new approaches. Methods: The main objective is to evaluate a new approach to cardiopulmonary resuscitation instruction using a self-instructional kiosk to teach Hands-Only CPR to people at a busy international airport. This is a prospective, observational study evaluating a new approach to teach Hands-Only CPR to the public from July 2013 to February 2016. The American Heart Association developed a Hands-Only CPR Kiosk for this project. We assessed the number of participants who viewed the instructional video and practiced chest compressions as well as the quality metrics of the chest compressions. Results: In a 32-month period, there were 23 478 visits to the Hands-Only CPR Kiosk and 9006 test sessions; of those practice sessions, 26.2% achieved correct chest compression rate, 60.2% achieved correct chest compression depth, and 63.5% had the correct hand position. Conclusions: There is noticeable public interest in learning Hands-Only CPR by using an airport kiosk and an airport is an opportune place to engage a layperson in learning Hands-Only CPR. The average quality of Hands-Only CPR by the public needs improvement and adding kiosks to other locations in the airport could reach more people and could be replicated in other major airports in the United States.